(untitled) (Research, Society and Development, 2020)
This study intends to search for public security indexes, focusing on Coutos and Fazenda Coutos districts, both on railroad suburb area, as also focusing on other districts from Salvador which have or not community bases, with the purpose to explain relations between crime reduction and advent of Community Police. It is a very relevant issue because public security, besides providing better life qualities to population, also promote social and economic development, brings the fighting against crime possible. An historical synthesis have been carried out about public security, with consonances of United Nations recommendations, that lead to analysis of peace dimensions, security and development, which provide strengthening of fundamental rights. In this way, it has been also presented some public security indexes with the attempt to clarify if Coutos and Fazenda Coutos community bases has positive or negative results. It has also been observed that the community bases of Coutos and Fazenda Coutos are given with better results, when compared with other neighborhoods in the Suburb of Salvador, about crime rates after the implementation of community police bases.